How Important of The Accuracy Sales Forecasting Method against Sales Strategy Decision Making of The Mobile Phone Network Operator Company: A Case Study - Alodya Agustina Elsam; Astrelia Crisentya Linardi; Liem Gai Sin (AIBPM Publisher, 2018)
This paper examinesthe accuracy of sales forecasting method that are important for decision making of sales strategy the mobile phone network operator company. Sales forecasting used to estimate company products sales for next year, so the company could make sales strategy plans and estimation an amount to be produced next year. Mobile phone network operator is one of un-seasonable products. The purpose of the paper is to compare, analyze, and giving a recommend of the best sales forecasting method to improve the mobile phone network operator company. Quantitative data were collected through published companies finnacial reports, articles, and journals which related with Supply Chain Management theory. The contribution this paper is providing the mobile phone network operator company to make successful sales strategy based from good sales forecasting method. Keywords – Sales Forecasting, Mobile Phone Network Operator Company, Sales Strategy, Forecasting Method